Strategi Perencanaan Pembangunan Infrastruktur dalam Meningkatkan Pertumbuhan Ekonomi di Kabupaten Gowa: Pendekatan Analisis SWOT - Almadhani, Muhammad Zarfan; Kamaruddin, Citra Ayni; Regina, Regina; Astuty, Sri; Bado, Basri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to formulate infrastructure development planning strategies to enhance economic growth in Gowa Regency. The research adopts a qualitative approach using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to identify internal and external factors influencing regional development planning. Data were collected through in-depth interviews with key informants from the Regional Development Planning Agency of Gowa Regency, supported by document analysis and relevant policy reviews. The findings indicate that Gowa Regency possesses significant internal strengths, including institutional capacity and integrated planning systems, as well as external opportunities such as its strategic position within the Mamminasata National Strategic Area and growing investment potential. However, several challenges remain, including limited budget capacity, uneven infrastructure distribution, and gaps between planning and implementation. Based on the SWOT matrix, the institution is positioned in Quadrant I, indicating an aggressive growth-oriented strategy. Therefore, the recommended strategies include strengthening economic infrastructure, enhancing institutional capacity, promoting community-based economic empowerment, and developing sustainable infrastructure. These findings are expected to provide a basis for improving the effectiveness of development planning and fostering inclusive economic growth.